A pan-tropical cascade of fire driven by El Niño/Southern Oscillation. Issue 12 (December 2017) - Chen, Yang; Morton, Douglas; Andela, Niels; van der Werf, Guido; Giglio, Louis; Randerson, James
Abstract The El Niño/Southern Oscillation (ENSO) has a pronounced influence on year-to-year variations in climate1 . The response of fires to this forcing2 is complex and has not been evaluated systematically across different continents. Here we use satellite data to create a climatology of burned-area and fire-emissions responses, drawing on six El Niño and six La Niña events during 1997–2016. On average, reductions in precipitation and terrestrial water storage increased fire emissions in pan-tropical forests by 133% during and following El Niño as compared with La Niña. Fires peaked in equatorial Asia early in the ENSO cycle when El Niño was strengthening (Aug–Oct), before moving to southeast Asia and northern South America (Jan–Apr), Central America (Mar–May) and the southern Amazon (Jul–Oct) during the following year. Large decreases in fire occurred across northern Australia during Sep–Oct of the second year from a reduced fuel availability. Satellite observations of aerosols and carbon monoxide provided independent confirmation of the spatiotemporal evolution of fire anomalies. The predictable cascade of fire across different tropical continents described here highlights an important time delay in the Earth system's response to precipitation redistribution. These observations help to explain why the growth rate of atmospheric CO2 increases during El Niño3 and may contribute to improved seasonal fire forecasts. Reductions in precipitation and water storage increased fire emissions in pan-tropical forests by 133% during and following El Niño events (1997–2016). Fires follow a predictable cascade across tropical continents that may improve seasonal fire forecasts.